Editorial: Immigrant and Ethnic Entrepreneurship - Jan Brzozowski (Entrepreneurial Business and Economics Review, 2015)
The importance of businesses started and developed by immigrants is host countries is substantial. Just in the US, 90 of the enterprises listed on Fortune 500 have been founded by immigrants, and additional 114 have been started by the second-generation immigrants, i.e. children of foreign-born persons (cf. Partnership for a New American Economy, 2011). As the contribution of immigrant entrepreneurship for the global economy is recognized by policy makers and experts, it is also reflected in the growing research on this topic. Research papers on immigrant and ethnic entrepreneurship have increased in numbers in 2000s and in the second decade of 21st century, including articles in such respected journals as Entrepreneurship Theory and Practice (Drori, Honig, & Wright, 2009), Small Business Economics (Mueller, 2014) or Entrepreneurship and Regional Development (Aliaga-Isla&Rialp, 2013).